Determination of Shape and Sphericity of Silicon Quantum Dots Imaged by EFTEM‐Tomography. Issue 12 (6th November 2017) - Hiller, Daniel; Gutsch, Sebastian; López‐Vidrier, Julian; Zacharias, Margit; Estradé, Sònia; Peiró, Francesca; Cruz‐Matías, Irving; Ayala, Dolors
Abstract : The shape of size‐controlled silicon nanocrystals (Si NCs) embedded in SiO2 is investigated by tomographic energy‐filtered transmission electron microscopy (EFTEM). The sphericity of the quantum dots is determined by computational analyses. In contrast to other fabrication methods, we demonstrate that the NCs in superlattices are non‐agglomerated, individual clusters with slightly oblate spheroidal shape. This allows for low surface‐to‐volume ratios and thereby low non‐radiative defect densities as required by optoelectronic or sensing applications. A near‐spherical shape is also a prerequisite for the direct comparison of Si quantum dots (QDs) with theoretical simulations. Abstract : Voxel model of the tomographic EFTEM‐reconstruction used in this study to analyze the shape of size‐controlled Si NCs.